Making two-channel pricing decisions in a multi-objective closed-loop supply chain network under uncertainty considering reliability (case study: steel industry) - Seyyed Edalatpanah; Nenad Komazec; Dragan Pamucar (Big Data and Computing Visions)
Today, according to the development of the steel industry around the world, the variety of products has increased, and the products have certain complications. Due to the variety of products in this industry, the need to organize the production and manufacture of parts is felt, but the organization of the supply of raw materials, machinery, and human resources has many problems. Different supply chain networks have emerged to organize such cases, each with unique advantages and characteristics. One of the most important supply chain networks is the green supply chain network, which deals with environmental aspects in addition to economic aspects. In supply chain networks, pricing on products is very important in conditions of uncertainty, and its impact on all supply chain decisions is evident. So, by increasing or decreasing the amount of demand as well as the price of products, its effect on the amount of distribution, production, and supply is evident. Considering the importance of pricing in the closed-loop supply chain, this article discusses modeling a two-objective problem with green product strategies and pricing in the supply chain with non-deterministic maintenance costs. The goal is to maximize the profit of the entire supply chain network and maximize reliability by making the right decisions on location, routing, allocation, and inventory.